Determination of solubility product of mercurous acetate at various ionic strengths in aqueous medium - deMoraes, M.; Pezza, Leonardo [UNESP]; Melios, C. B.; Molina, M.; Pezza, Helena Redigolo [UNESP]; Peres, A. M.; Villafranca, A. C.; Carloni, J. (Editora Unesp, 1996)
The conditionals (K-ps) and thermodynamics (K-ps(o)) solubility products of mercurous acetate have been determined, in aqueous solution, at 25 degrees C and ionic strength (I) comprised between 0.300 and 3.000 mol/L (NaClO4). The investigation was carried out potentiometrically by using a second class electrodes which responds to acetate ions. The values obtained for [pK(ps) (I)] were: 9.49+/-0.08 (0.000); 9.51+/-0.08 (0.300); 9.53+/-0.08 (0.500); 9.54+/-0.08 (0.700); 9.55+/-0.09 (0.900), 9.57+/-0.09 (1.200); 9.59+/-0.10(1.500); 9.61+/-0.10 (1.800); 9.63+/-0.10 (2.100); 9.65+/-0.11 (2.400); 9.67+/-0.11 (2.700) e 9.69+/-0.12 (3.000).
Keywords: solubility products; mercurous acetate; potentiometry; ionic strength; acetate second class electrodes